1998
DOI: 10.1046/j.1365-2133.1998.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Seborrhoeic dermatitis is not caused by an altered immune response toMalasseziayeast

Abstract: The immune response of patients with seborrhoeic dermatitis and healthy age- and sex-matched controls was examined to test the hypothesis that an inadequate or inappropriate immune response to Malassezia yeast leads to seborrhoeic dermatitis. Antibody responses were examined using enzyme-linked immunosorbent assays (ELISAs) and Western blots and lymphocyte responses using lymphocyte proliferation assays. The level of IgG and IgM specific for whole yeast cells or extracted proteins of two isolates of M. furfur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 35 publications
2
37
0
2
Order By: Relevance
“…but rather an alteration in cellular immune response. 81,82 Neuber et al also reported an alteration in cellular immunity in SD. 83 Watanabe et al showed that M. furfur does not lead to cytokine production by the keratinocytes, whereas this occurs with the other species of Malassezia.…”
Section: Immunogeneticsmentioning
confidence: 98%
“…but rather an alteration in cellular immune response. 81,82 Neuber et al also reported an alteration in cellular immunity in SD. 83 Watanabe et al showed that M. furfur does not lead to cytokine production by the keratinocytes, whereas this occurs with the other species of Malassezia.…”
Section: Immunogeneticsmentioning
confidence: 98%
“…The most recent study, in 1998, found no significant differences in titers of IgG or IgM antibody between patients and controls (328). Western blots using the cytoplasmic antigen demonstrated recognition of bands ranging from around 30 kDa to over 116 kDa.…”
Section: Seborrheic Dermatitis and Dandruffmentioning
confidence: 99%
“…However, there is no definitive evidence supporting the association of SD with this pathogen. Several studies focusing on quantitative or qualitative determinations of yeasts and on the immune response to P. ovale in patients with SD produced conflicting results (18)(19)(20)(21). The association ofthis pathogen with SD rests mainly on the results of therapeutic studies demonstrating the efficacy of antifungal agents, especially ketoconazole (22)(23), which, otherwise, has an additional antiinflammatory activity (24)(25).…”
Section: Discussionmentioning
confidence: 99%